2017
DOI: 10.18632/oncotarget.17242
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and survival outcomes in endocrine-related gynecologic cancers: A systematic review and meta-analysis

Abstract: Previous studies investigating the association between statin use and survival outcomes in gynecologic cancers have yielded controversial results. We conducted a systematic review and meta-analysis to evaluate the association based on available evidence. We searched the databases of the Cochrane Central Register of Controlled Trials (CENTRAL), Embase, and PubMed from inception to January 2017. Studies that evaluated the association between statin use and survival outcomes in gynecologic cancers were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 55 publications
0
18
2
Order By: Relevance
“…Lipids, including cholesterol and fatty acids, have been shown to play tumor-promoting roles in many cancers, including EOC [ 48 – 50 ]. Statins have been used in the management of several cancers [ 51 , 52 ] Statins target HMG-CoA reductase (Hmgcr), which is the rate-limiting enzyme for cholesterol synthesis. However, data exist showing that statins may have negative impacts in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Lipids, including cholesterol and fatty acids, have been shown to play tumor-promoting roles in many cancers, including EOC [ 48 – 50 ]. Statins have been used in the management of several cancers [ 51 , 52 ] Statins target HMG-CoA reductase (Hmgcr), which is the rate-limiting enzyme for cholesterol synthesis. However, data exist showing that statins may have negative impacts in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding OC survival studies, the overall survival (OS) rate for post diagnostic patients is significantly higher in statins users (hazard ratio (HR)) = 0.63; 95% confidence interval (CI) = 0.54–0.74 [ 58 ]; HR = 0.87; 95% CI = 0.80–0.95 [ 59 ]) compared to non-users. Other studies show that statin users present all-cause mortality and cancer-related mortality rates significantly lower (HR = 0.72; 95% CI = 0.56–0.93 [ 60 ]; HR = 0.85; 95% CI = 0.82–0.87 [ 61 ]) compared to non-users.…”
Section: Drug Repurposing For Ovarian Cancer Therapymentioning
confidence: 99%
“…In fact, for 13 types of cancers, it was observed a decrease in cancer-related death risk in statin users [ 61 ]. The anti-tumoral effects of statins has also been described in variety of other cancer origins, for example, endometrial cancer (HR = 0.83; 95% CI = 0.69–1.01) [ 58 ], breast cancer (HR = 0.81; 95% CI = 0.68–0.96) [ 64 ], colorectal cancer (fully adjusted HR = 0.71; 95% CI = 0.61–0.84) [ 65 ] and prostate cancer (HR = 0.76; 95% CI = 0.66–0.88) [ 66 ]. These studies show the effect of statins to prevent the onset of cancer.…”
Section: Drug Repurposing For Ovarian Cancer Therapymentioning
confidence: 99%
“…Other meta-analyses and review articles on gynecological cancers, such as breast and endometrial, have demonstrated that statin consumption generally has substantial survival-related benefits in terms of both disease-specific survival and overall survival, contributing to both pre- and post-diagnosis statin consumption [ 48-50 ]. Other meta-analyses have suggested that statin consumption is associated with an increase in survival for lung cancer [ 50 ], esophageal cancer [ 51 ], pancreatic cancer [ 52 , 53 ] and endocrine-related gynecologic cancers [ 54 ].…”
Section: Discussionmentioning
confidence: 99%